SUMBER DAYA MANUSIA BERMARTABAT: DARI TEKNOKRATIK KE KARAKTER - I Wayan Gede Suacana (Universitas Warmadewa, 2016)
Orthodoxy is the present state that we must prepare to face the challenges of the age symbolized by the new mysticism, the number